Phenomenology/ontopoiesis retrieving geo-cosmic horizons of antiquity logos and life - Tymieniecka, Anna-Teresa (Analecta Husserliana, The Yearbook of phenomenological research, 2011)
Continental philosophy continues to be rooted in the ancient Greek principle of the Logos, which subtends our conception of rationality of all things. However, the crucially significant for the Greek thought innermost essential linking between the human soul and the cosmos ? as the heart of metaphysics ? has not been significantly pursed, leaving an essential area of the Logos? dominion neglected. Contemporary science revealing the grounding principles of becoming uncovers the Logos hidden in our dealings with earth in its interlacings with the skies. Logos in the ontopoiesis of life opens through its trajectories of becoming its full horizon?so long closed toward future of the fulfilled metaphysics. The controversy of flux and stasis as the groundwork of reality of Greek ancient philosophy reached its crux in the all encompassing doctrine of the logos by Heraclitus of Ephesus. It centers upon human soul in its role with the cosmos. Philosophy of the Occident corroborating Greek insights with the progress of culture in numerous interpretations (Kant, Kierkegaard, Husserl, Merleau-Ponty, Ricoeur?), presented in this collection has neglected the cosmic sphere. While contemporary development of science revealed its grounding principles (papers by Grandpierre, Kule and Trutty-Coohill) the ancient logos fully emerges. Thus, logos hitherto hidden in our commerce with earth is revealed in its intertwinings with the cosmos through the trajectories of the phenomenology/ontopoiesis of life (Tymieniecka). The crucial link between the soul and the cosmos, in a new geo-cosmic horizon, is thus being retrieved.